2020
DOI: 10.7717/peerj.8256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental variables on abundance of ammonia-oxidizing communities in sediments of Luotian River, China

Abstract: Ammonia-oxidizing communities play important functional roles in the nitrification. However, environmental stresses can significantly affect this process by controlling the abundant communities of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) communities. In this study, we examined the abundance variations of ammonia-oxidizing communities using quantitative polymerase chain reaction (qPCR) and terminal-restriction fragment length polymorphism (T-RFLP) in a typical subtropical river, Luot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…The predominant t-RF 162 in both cropland and grassland soils could be explained by the features of different members of Candidatus Nitrososphaera, that are capable of biofilm formation, detoxification and adhesion, thus they are well adapted to environmental changes (Hammerl et al, 2019;Kerou et al, 2016). Moreover, the members of Thaumarchaeota, for example several species classified in the Nitrosotalea genus, may be adapted to acidic environments with a pH lower than 6.5 (Ginawi et al, 2020), therefore in our study their representatives were found in both tested sandy acidic soils under cropland and grassland. It should be taken into consideration that the assignment of archaeal community was based on databases in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant t-RF 162 in both cropland and grassland soils could be explained by the features of different members of Candidatus Nitrososphaera, that are capable of biofilm formation, detoxification and adhesion, thus they are well adapted to environmental changes (Hammerl et al, 2019;Kerou et al, 2016). Moreover, the members of Thaumarchaeota, for example several species classified in the Nitrosotalea genus, may be adapted to acidic environments with a pH lower than 6.5 (Ginawi et al, 2020), therefore in our study their representatives were found in both tested sandy acidic soils under cropland and grassland. It should be taken into consideration that the assignment of archaeal community was based on databases in silico analysis.…”
Section: Discussionmentioning
confidence: 99%
“…It should be taken into consideration that the assignment of archaeal community was based on databases in silico analysis. However, the presence of Candidatus Nitrososphaera, Candidatus Nitrosoarchaeum limnia, Nitrosopumilus sp., Candidatus Nitrosotenuis and Candidatus Nitrosotalea were detected in different sediment and soil environments (Hammerl et al, 2019;Cao et al, 2012;Ginawi et al, 2020;Wessén et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent that AOB and AOA drive the ammonia-oxidizing process, a rate-limiting phase in nitrification processes [14,15]. Most studies have focused on the dispersion and role of oxidizers of oxidizers (AOA and AOB) in diverse ecosystems [16,17]. For instance, mounted evidence indicates that the AOA dominates the soil ecosystems, displaying a greater quantity and a richer diversity of communities than the AOB [18].…”
Section: Introductionmentioning
confidence: 99%